PERAN HUMAS RADIO ‘JAWA’ SAFARI 1134 AM DALAM MENJALIN KERJASAMA DENGAN BANK JATENG - Riyodina Pratikto (Avant Garde, 2016)
Radio 'Java' Safari 1134 AM is one of the private radio station in Jakarta. Radio 'Java' Safari 1134 AM have a Public Relations role in cooperating with the audience. In this study Radio 'Java' Safari 1134 AM cooperating with the Bank Central Java. Cooperation undertaken Radio 'Java' Safari 1134 AM with the Bank of Central Java in the form of services, through the promotion and publicity programs and products Bank Central Java. This study aims to determine how the role of the Public Radio 'Java' Safari 1134 AM in cooperation with Bank Central Java. Formulation of the problem is "What is the Role of Public Relations Radio 'Java' Safari 1134 AM in cooperation with the Bank Central Java" This research method is descriptive qualitative. These results indicate that, the Role of Public Relations' Radio 'Java' Safari 1134 AM in cooperation with the Bank of Central Java PR act as Communicator, Public Relations Radio 'Java' Safari 1134 AM establish communication with the Bank of Central Java in terms of offering cooperation Relationship through relationships forged as foster mutual friendship, hold a lunch or a coffee break and discipline at the time meet and also broadcasts time. Good Image Maker to build a positive image. Cooperation is carried out through the promotion and publicity of products and programs Bank of Central Java to the listeners of Radio 'Java' Safari 1134 AM in order to aim the listener or the public can find products and programs Bank Central Java opening up the opportunity for the listener to be able to join and become a new customer of Bank of Central Java , Cooperation Radio 'Java' Safari 1134 AM with Bank Central Java has existed long enough, and under this agreement the two sides benefited. Radio 'Java' Safari 1134 AM is able to maintain good relations with Bank Central Java that cooperation still runs today. This research was conducted in October-November, 2016.